Caffeinated energy drink intoxication. Issue 8 (25th July 2011) - Trabulo, Daniel; Marques, Susana; Pedroso, Ermelinda
Abstract : Summary: In recent years an increasing number of different energy drinks have been introduced to provide an energy boost. They contain high levels of caffeine and other additives that act as stimulants. Several recent studies present that energy drinks could increase the risk of seizures, acid-base disorders and cardiovascular events. The authors report a 28-year-old man who was brought to the emergency room after sudden onset of tonic-clonic seizures and metabolic acidosis after drinking several cans of a caffeinated energy drink. The authors believe that this clinical picture was caused by caffeine intoxication from an energetic drink causing a syndrome of catecholamine excess. The patient was discharged within a week with no complaints and no neurological signs. Finally, recognising the features of caffeine intoxication and its potential health consequences may be especially relevant when treating younger persons who may be more likely to consume energy drinks.